A correction algorithm for stereo matching with general digital cameras and web cameras. (1st January 2013) - Sun, Ningping; Murakami, Soichiro; Nagaoka, Hiroshi; Shigemoto, Takuya
We introduce stereo matching into our 3D computer graphics modelling because of its good interaction and convenience. Instead of the special standard stereo camera we evolve a network that consists of a series of the general digital cameras and web cameras and apply it to 3DCG modelling and motion capture. In this paper we propose a stereo axes correction algorithm to resolve the non-paralleled axes problem of the traditional stereo matching method and examine our new equations with experimental results.